2002
DOI: 10.1046/j.1365-2958.2002.03087.x
|View full text |Cite
|
Sign up to set email alerts
|

SakA MAP kinase is involved in stress signal transduction, sexual development and spore viability in Aspergillus nidulans

Abstract: SummaryIn eukaryotic cells, environmental stress signals are transmitted by evolutionarily conserved MAPKs, such as Hog1 in the budding yeast Saccharomyces cerevisiae, Spc1 in the fission yeast Schizosaccharomyces pombe and p38/JNK in mammalian cells. Here, we report the identification of the Aspergillus nidulans sakA gene, which encodes a member of the stress MAPK family. The sakA gene is able to complement the S. pombe spc1 -defects in both osmoregulation and cell cycle progression. Moreover, SakA MAPK is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
238
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(248 citation statements)
references
References 47 publications
(79 reference statements)
7
238
2
1
Order By: Relevance
“…Commercially available antibodies against mammalian or S. cerevisiae MAPKs were used to detect phospho-OS-2 (anti-p38 9211; 1:1000 dilution; Cell Signaling Technology, Beverly, MA; Kawasaki et al, 2002), and OS-2 (anti-Hog1p sc-9079; 1:600 dilution; Santa Cruz Biotechnology, Santa Cruz, CA). Incubation with secondary antibody and chemiluminescent detection were performed as described previously (Krystofova and Borkovich, 2005).…”
Section: Phenotypic Testing and Western Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Commercially available antibodies against mammalian or S. cerevisiae MAPKs were used to detect phospho-OS-2 (anti-p38 9211; 1:1000 dilution; Cell Signaling Technology, Beverly, MA; Kawasaki et al, 2002), and OS-2 (anti-Hog1p sc-9079; 1:600 dilution; Santa Cruz Biotechnology, Santa Cruz, CA). Incubation with secondary antibody and chemiluminescent detection were performed as described previously (Krystofova and Borkovich, 2005).…”
Section: Phenotypic Testing and Western Analysismentioning
confidence: 99%
“…Anti-Hog1p recognizes both nonphosphorylated and phosphorylated forms of the protein, whereas anti-phospho p38 is specific for the phosphorylated MAPK. The phosphop38 antibody was previously shown to cross-react with the homologous MAPK protein, SakA, from Aspergillus nidulans (Kawasaki et al, 2002), whereas both antibodies were shown to recognize the homologous MAPK protein OSC-1 from Colletotrichum lagenarium (Kojima et al, 2004). We tested the antibodies for binding to OS-2 via Western analysis of extracts from wild-type, ⌬rrg-1, and os-2 strains (Figure 4, A-C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Hog1 MAPK pathway also plays a pivotal role in fungicides susceptibility. Hog1 mutants of fungi like Fusarium proliferatum (Ádám et al, 2008), Aspergillus nidulans (Kawasaki et al, 2002), C. heterostrophus (Igbaria et al, 2008) and C. lagenarium (Kojima et al, 2004) all showed tolerant to phenylpyrrole and dicarboximide fungicides. In A. alternata, the AaHog1 mutants were also resistant to dicarboximide and phenylpyrrole fungicides, but the induced level of resistance was very small, implying another signaling pathway in response to these fungicides stress (Lin and Chung, 2010).…”
mentioning
confidence: 99%
“…(Ronen et al, 2007). Além disso, esta via está envolvida no crescimento polarizado, morfogênese (Donen et al, 2007;Teepe et al, 2007), utilização de açúcares (Reyes et al, 2006), estresse osmótico e oxidativo (Davenport et al, 1995;Han e Prade, 2002;Kawasaki et al, 2002;Furukawa et al, 2005), desenvolvimento sexual e viabilidade dos esporos (Kawasaki et al, 2002;Ichinomiya et al, 2007) e produção de penicilina (Herrmann et al, 2006). A via PKC/MAPK é requerida na transdução da resposta a presença do farnesol em células de mamíferos, S. cerevisiae, C.…”
Section: -Peptídeo Sinal E Via Secretóriaunclassified